Self Improvement Strategy of Educational Organization in the Age of Globalization - Rengkamon, Paitoon (Journal of Advanced Development in Engineering and Science, 2023)
Due to the scope and content of the new jobs, functions and tasks for the new facet of education services on the era of globalization are needed to be developed and designed. Then administrators have to know the strategy to improve the educational organization as well as to be able to develop the proper motivational scheme, the appropriate leadership style, and the skill of task delegation, supervision, and training activities. The fairness and equity must be employed to attain the better fringe benefit and promotion system at the competitive world.